Application of Aluminum Nanopowder for Pure Hydrogen Production; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Ilyin A. P. Aleksandr Petrovich (Materials and Technologies in Powder Metallurgy and Additive Manufacturing, 2016)
Title screen